(untitled) (Eurasian Journal of History, Geography and Economics, 2024)
This article presents a scientific analysis of the history of the development of the chemical industry of Uzbekistan, its territorial structure, current problems and future directions of development. The article describes the relationship between the territorial location of the chemical industry and the factors that shape it, including natural resources, infrastructure, and economic regions. The activities of industrial centers such as Chirchik, Fergana, Navoi and Shortan are analyzed in detail, and their importance in the local and international market is shown. Also, the article describes in detail the main problems in the development of the industry, including outdated technologies, shortage of personnel, issues of environmental safety and insufficient processing of resources. Directions such as introduction of modern technologies, provision of environmental safety, training of personnel, promotion of scientific research and expansion of international cooperation are offered as prospects for development